O-GlcNAcylation stabilizes β-catenin through direct competition with phosphorylation at threonine 41 - Olivier-Van Stichelen, Stéphanie (Federation of American Societies for Experimental Biology, 2014)
Dysfunctions in Wnt signaling increase β-catenin stability and are associated with cancers, including colorectal cancer. In addition, β-catenin degradation is decreased by nutrient-dependent O-GlcNAcylation. Human colon tumors and colons from mice fed high-carbohydrate diets exhibited higher amounts of β-catenin and O-GlcNAc relative to healthy tissues and mice fed a standard diet, respectively. Administration of the O-GlcNAcase inhibitor thiamet G to mice also increased colonic expression of β-catenin. By ETD-MS/MS, we identified 4 O-GlcNAcylation sites at the N terminus of β-catenin (S23/T40/T41/T112). Furthermore, mutation of serine and threonine residues within the D box of β-catenin reduced O-GlcNAcylation by 75%. Interestingly, elevating O-GlcNAcylation in human colon cell lines drastically reduced phosphorylation at T41, a key residue of the D box responsible for β-catenin stability. Analyses of β-catenin O-GlcNAcylation mutants reinforced T41 as the most crucial residue that controls the β-catenin degradation rate. Finally, inhibiting O-GlcNAcylation decreased the β-catenin/α-catenin interaction necessary for mucosa integrity, whereas O-GlcNAcase silencing improved this interaction. These results suggest that O-GlcNAcylation regulates not only the stability of β-catenin, but also affects its localization at the level of adherens junctions. Accordingly, we propose that O-GlcNAcylation of β-catenin is a missing link between the glucose metabolism deregulation observed in metabolic disorders and the development of cancer.—Olivier-Van Stichelen, S., Dehennaut, V., Buzy, A., Zachayus, J.-L., Guinez, C., Mir, A.-M., El Yazidi-Belkoura, I., Copin, M.-C., Boureme, D., Loyaux, D., Ferrara, P., Lefebvre, T. O-GlcNAcylation stabilizes β-catenin through direct competition with phosphorylation at threonine 41.